Penerapan Lean Kaizen untuk Meningkatkan Produktivitas Line Painting pada Bagian Produksi Automotive dengan Metode PDCA - Kartika, Hayu (Jurnal Sistem Teknik Industri, 2020)
This paper was conducted in the automotive industry, the purpose of this study was to improve the productivity of workmanship in the Line Painting process in the production department. The focus of this research is: to see the waste that occurs in this part of the process this is because in the process productivity is still far below the target set by the company, so it needs to be improved in the process. Improvements were made using the Lean concept combined with the PDCA method. From the results of repairs carried out, it was found that during the Line Painting process there was a lot of waste loss time, then improvements were made with the application of Lean to get an increase or improvement in productivity by 80.6% which previously productivity only reached 71%. From this research it is proven that by implementing Lean, this can significantly increase productivity